A new Sun: Probing solar plasmas in the extreme-ultraviolet light from SUMER on SOHO - Dwivedi B.N.; Mohan A.; Wilhelm K. (My University, 2025)
We briefly outline the extreme-ultraviolet spectroscopy of solar plasmas in the light of a wealth of high-resolution observations, both in spectral and spatial regimes, from the SUMER spectrograph (Solar Ultraviolet Measurements of Emitted Radiation) on the spacecraft SOHO (Solar and Heliospheric Observatory). We then present some of the new results on a new Sun seen by the SUMER spectrograph. In particular, we discuss coronal holes and the solar wind, the 'red'/'blue' Sun, abundance anomalies, explosive events and sunspot transition region oscillations. We conclude this article by reiterating clues, obtained from SUMER, that provide information essential for solving solar riddles of coronal heating and the wind acceleration.